APLIKASI THEORY OF PLANNED BEHAVIOR DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUSU CAIR DALAM KEMASAN PADA MAHASISWA INDONESIA DAN MALAYSIA - Rofikah Fitriana; Suprehatin Suprehatin (Jurnal Agribisnis Indonesia, 2018)
The consumption rate of milk in Indonesia is still lower than other countries in ASEAN, including Malaysia. A geographical difference makes the consumer of packaged milk of both countries have different behavior in purchasing decisions. According to the theory of planned behavior (TPB), the purchasing decision was formed by intention that is influenced by attitude toward behavior, subjective norm, and perceived behavioral control. Product attributes such as price, brand and packaging were also considered to influence the purchasing decision. This research aims to examine the effects of theory of planned behavior and product attribute on purchase decision of packaged liquid milk products towards Indonesian and Malaysian undergraduate students. The empirical research builds on an online survey with a sample of 200 undergraduate students. The results from the structural-equation modeling confirm that the significant variables on TPB for Indonesian students were attitude toward behavior and perceived behavioral control, and for Malaysian students were attitude toward behavior, subjective norm, and perceived behavior control. The significant variables on product attributes for Indonesian students were the brand and product quality, and there was no significant variable for Malaysian students.